Innovation and Policing: Factors Influencing the Adoption of Social Medias by Members of Quebec Police Organizations. (20th October 2018) - Delle Donne, Julie; Fortin, Francis
Abstract: The literature on members of police organizations adopting new technology is generally descriptive and rarely explanatory. However, the Diffusion of Innovation Theory and the studies that have grown out of it have contributed to creation of a model that helps explain adoption rates of new technology by individuals working in an organization. To verify whether this model can be used to study the adoption of technology in police organizations, our study examines the factors that influence the adoption of social media (SM) by members ( n = 177) of Quebec police organizations. Our findings confirm that the factors identified in the literature on innovation—the perception that potential users have of the new technology as well as organizational factors, such as the respondent's role in the organization—can also help explain why and how frequently a member uses SM in his or her work.